(−)‐Epicatechin Rescues Memory Deficits by Activation of Autophagy in a Mouse Model of Tauopathies - Yanqing Wu; Ting Li; Xingjun Jiang; Jianmin Ling; Zaihua Zhao; Jiahui Zhu; Chongyang Chen; Qian Liu; Xifei Yang; Xuefeng Shen; Rong Ma; Gang Li; et al. (MedComm)
ABSTRACT In tauopathies, defects in autophagy‐lysosomal protein degradation are thought to contribute to the abnormal accumulation of aggregated tau. Recent studies have shown that (−)‐Epicatechin (Epi), a dietary flavonoid belonging to the flavan‐3‐ol subgroup, improves blood flow, modulates metabolic profiles, and prevents oxidative damage. However, less research has explored the effects of Epi on tauopathies. Here, we found that Epi rescued cognitive deficits in P301S tau transgenic mice, a model exhibiting characteristics of tauopathies like frontotemporal dementia and Alzheimer's disease, and attenuated tau pathology through autophagy activation. Proteomic and biochemical analyses revealed that P301S mice exhibit deficits in autophagosome formation via modulating mTOR, consequently inhibiting autophagy. Epi inhibited the mTOR signaling pathway to promote autophagosome formation, which is essential for the clearance of tau aggregation. By using chloroquine (CQ) to inhibit autophagy in vivo, we further confirmed that Epi induced tau degradation via the autophagy pathway. Lastly, Epi administration was also found to improve cognition by reversing spine decrease and neuron loss, as well as attenuating neuroinflammation. Our findings suggest that Epi promoted tau clearance by activating autophagy, indicating its potential as a promising therapeutic candidate for tauopathies.